Work‐related risk factors for lateral epicondylitis and other cause of elbow pain in the working population1. Issue 4 (13th November 2012) - Herquelot, Eleonore; Bodin, Julie; Roquelaure, Yves; Ha, Catherine; Leclerc, Annette; Goldberg, Marcel; Zins, Marie; Descatha, Alexis
Abstract Background This study was designed to assess the relationship between work‐related combined physical and psychosocial factors and elbow disorders (lateral epicondylitis and non‐specific disorders without lateral epicondylitis) in the working population. Methods A total of 3, 710 workers (58% men) in a French region in 2002–2005 participated in physical examinations by occupational health physicians and assessed their personal factors and work exposure by self‐administered questionnaire. Statistical associations between elbow disorders and risks factors were analyzed using multinomial logistic regression. Results A total of 389 (10.5%) workers had elbow pain without lateral epicondylitis and 90 (2.4%) workers had lateral epicondylitis. Age, body mass index (>25), and low social support (only for men) were significant risks factors. Hard perceived physical exertion combined with elbow flexion/extension (>2 hr/day) and wrist bending (>2 hr/day) was a strong significant risk factor for elbow pain and epicondylitis: among men, adjusted Odds Ratio (ORa) = 2.6 (1.9–3.7) and ORa = 5.6 (2.8–11.3), respectively; among women, ORa = 1.4 (0.9–2.2) and ORa = 2.9 (1.3–6.5). Conclusions This study emphasizes the strength of the associations between combined physical exertion and elbow movements and lateral epicondylitis. Certain observed differences in associations with lateral epicondylitis and elbow pain only indicate the need for additional longitudinal studies on different stages of elbow disorders and known risk factors. Am. J. Ind. Med. 56:400–409, 2013. © 2012 Wiley Periodicals, Inc.